Identifikasi Spesies Tanaman Penutup Tanah pada Perkebunan Kelapa Sawit Menghasilkan - Suryana; Chozin, Muhamad Achmad; Guntoro, Dwi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
The study aimed to identify the types of plants suitable for cover crops on mature oil palm. The study was started by conducting microclimate measurements and vegetation analysis in a mature oil palm ecosystem with plant subjects consisting of 5 years and 10 years old plants. The measurements and analysis were carried out in August 2018 to select suitable plant samples. The research was continued by planting 6 selected plants under the shade of 0, 25, 50, and 75% using nested design to determine the responses of plant samples to various levels of shading from September 2018 to April 2019 at the Cikaawang IPB Experimental Field. The results of microclimate analysis in 5-year-old mature oil palm in Jonggol shows the light intensity of 1094.7 lux with a temperature of 28.5 oC and humidity of 68.76%, while a 10-year-old mature oil palm in Cikabayan had a light intensity of 997.8 lux with a temperature of 32.5 oC and humidity of 87.25%. The species of Asystasia gangentica, Axonopus compressus, Borreria alata, and Ottochloa nodosa were the dominant plant vegetation in two ecosystems. Asystasia gangentica was able to grow and optimally cover the area at all shading levels, while Axonopus compressus, Borreria alata, and Ottochloa nodosa can only grow and cover the area optimally at 0% and 25% and 50% shade, respectively. Keywords: micro climate, response of plant species, vegetation analysis